The possibility of using autoclaved aerated concrete in buildings in hot environments (case of study is Sebha city) - Al Ashoush, Louy; Al Sharef, Mohammed Al Wally (Journal of Pure & Applied Sciences, 2023)
Building technology is accelerating globally in introducing new materials and theories in a world that seeks to achieve more sustainability in the same field, while preserving the functional goals and making the best use of buildings and achieving the comfort of users, and by looking at the hot desert climatic reality experienced by the people living in the south of Libya, systems and materials construction used in it. It was necessary to search for alternative building materials for those currently used to face the thermal differences that vary between a temperature of "44.2º in summer & 2.29º in winter" in order to achieve the concept of thermal comfort in residential buildings and other buildings .Accordingly, through the in-depth study of the researchers in the properties of the autoclaved concrete material "autoclaved aerated concrete or AAC" and its application globally and regionally in climates similar to the city of Sebha, and the use of the descriptive and analytical approach to research. The results of the study showed that the AAC reduced the value of the external heat transfer coefficient from 1.93 W/m²k for the cement block wall to 0.58 W/m²k, and reduced by 23.25% the number of unfulfilled cooling hours with the same thickness for the same void. The study also concluded that it is possible The use of this material in the future in the construction of buildings in Libya, especially in the southern region.